Aktualisasi Nilai Pancasila Sila Persatuan Melalui Sikap Toleransi Siswa SDN Angke 05 - Maratun Nafiah; Sutrisno Sutrisno; Dita Tri Rosmana (SAP (Susunan Artikel Pendidikan), 2022)
Indonesia as a pluralistic country is faced with a dilemma. The differences are a challenge as well as a threat to national unity. Pancasila has National values that should be applied to deal with the dilemmatic conditions of life of Indonesian. This study aims to describe the actualization of the values of the Pancasila through an attitude of tolerance in fifth grade elementary school students. This study used qualitative research methods. The data were obtained through observation, interviews, and document studies. The interview was conducted by making the fifth grade teacher the main informant. Other parties as informants were the principal and fifth grade students of SDN Angke 05 Pagi. The actualization of principle unity from the values of Pancasila in Angke 05 Pagi State Elementary School students is carried out through mutual respect and appreciation, acknowledging everyone's rights, respecting other people's beliefs, understanding each other, and also caring for each other even though there are differences.